Identifikasi Jenis dan Nilai Indeks Keanekaragaman Ekosistem Mangrove di Kelurahan Barombong Kecamatan Tamalate Kota Makassar - Fathuddin; Isman, Muhammad; Januar Noor, Rahmat (Jurnal Riset Diwa Bahari (JRDB), 2023)
The mangrove ecosystem is one of the key ecosystems on the coast which is an indicator of the environmental health of a coastal area. The coast of Makassar City is experiencing very rapid structural development marked by reclamation. This condition causes the existence of the mangrove ecosystem on the coast of Makassar City to be increasingly threatened. This study aims to determine the condition of the type and distribution of mangroves in the Barombong sub-district of Tamalatea, Makassar. The research was conducted from March to May 2023 in Tamalatea coastal area, Makassar. This research is an exploratory study conducted by survey method. The results of the study obtained four types of true mangroves and seven types of associated plants. The results obtained Rhizophora mucronata species have the highest value on the relative frequency index, relative dominance, relative density, and important value index.